\(x^2+y^2+\frac{1}{x^2}+\frac{1}{y^2}=4\)
\(\Leftrightarrow x^2+y^2+\frac{1}{x^2}+\frac{1}{y^2}-4=0\)
\(\Leftrightarrow\left(x^2-2.x.\frac{1}{x}+\frac{1}{x^2}\right)+\left(y^2-2.y.\frac{1}{y}+\frac{1}{y^2}\right)=0\)
\(\Leftrightarrow\left(x-\frac{1}{x}\right)^2+\left(y-\frac{1}{y}\right)^2=0\)(1)
Ta thấy \(\left(x-\frac{1}{x}\right)^2\ge0;\left(y-\frac{1}{y}\right)^2\ge0\forall x;y\) nên \(\left(x-\frac{1}{x}\right)^2+\left(y-\frac{1}{y}\right)^2\ge0\forall x;y\)
Để (1) xảy ra \(\Leftrightarrow\hept{\begin{cases}\left(x-\frac{1}{x}\right)^2=0\\\left(y-\frac{1}{y}\right)^2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=\frac{1}{x}\\y=\frac{1}{y}\end{cases}\Rightarrow\hept{\begin{cases}x=1\\y=1\end{cases}}}\)
Vậy \(x=y=1\)